Bukti Baru Monday Effect di Bursa Efek Indonesia (BEI) - Sagai, Rilie Tirza Liliroyor (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
ABSTRACT The aim of this research is about review whether the day of the week effect, monday effect, monthly effect and rogalski effect still exist in several indexes at BEI or not by analyzing return in conjunction with another look of monday effect from bid ask spread and trading volume especially for index LQ45. Furthermore to accomplish this reseach, better to know about the preference of investors on monday in order to know what do they prefer? Either sell or buy stock. The sample in this research is all stocks listed at IHSG, LQ45 and KOMPAS 100 for 2 years (2011 to 2012) and the methods of measurement used in review the day of the week effect, monday effect, monthly effect, rogalski effect, and the preference of investors on monday are four methods. They are, Kruskal-Wallis Test, Mann-Whitney Test, Regression and Wilcoxon Signed Rank Test. The results are, there is no different from bid ask spread in every single trading day but trading volume was proved smallest on monday and it was clearly made a phenomenon of the day of the week effect and monday effect still exist at Indonesia capital market (BEI). Even so, the phenomenon of monthly effect and rogalski effect were not proved. Furthermore, in LQ45 found that offer volume excess bid volume in every single trading day and it means that the investor is more prefer to sell stocks than buy stocks. Keywords : day of the week effect, monday effect, monthly effect, rogalski effect, bid ask spread, trading volume, the preference of investors on mondays. Â ABSTRAK Penelitian ini bertujuan untuk mengkaji ulang fenomena day of the week effect, monday effect, monthly effect dan rogalksi effect sekaligus dengan menguji sisi lain dari monday effect yaitu bid ask spread (BAS) dan volume perdagangan khususnya pada saham-saham indeks LQ45 untuk melihat eksistensi dari fenomena tersebut di BEI dan kaitan bid ask spread dan volume perdagangan saham harian terhadap fenomena tersebut. Selanjutnya untuk menyempurnakan penelitian ini, maka dilakukan pengujian mengenai minat jual dan beli saham investor di hari senin. Sampel dari penelitian ini adalah IHSG, LQ45 dan KOMPAS100 pada periode tahun 2011 sampai 2012 dan teknik analisis yang digunakan ada 4 macam yaitu Kruskal Wallis Test, Mann Whitney Test, Regression, dan Wilcoxon Signed Rank Test. Hasil penelitian menunjukkan bahwa tidak ditemukan perbedaan bid ask spread di setiap hari perdagangan, tetapi volume perdagangan terbukti berbeda dan lebih kecil di hari senin yang menyebakan terjadinya fenomena day of the week effect dan monday effect pada IHSG, LQ45, dan KOMPAS100. Sedangkan untuk monthly effect dan rogalski effect tidak ditemukan dalam penelitan ini. Selain itu, minat jual investor terbukti lebih besar daripada minat beli investor di perdagangan hari senin. Kata kunci: day of the week effect, monday effect, monthly effect, rogalski effect, bid ask spread, trading volume, minat jual dan beli investor.